World Bank East Asia and Pacific Economic Update, April 2013 : A Fine Balance - World Bank (Washington, DC, 2013)
The developing economies of the East Asia and Pacific (EAP) region grew by 7.5 percent in 2012, lower than the 8.3 percent growth recorded in 2011, but still higher than that of any other region. Within the region, available data in the first quarter of the year indicate that external weakness may be abating, while domestic demand remains resilient. The expectation of some stabilization in external demand, coupled with still resilient domestic activity, may be showing in the industrial production and purchasing manager's index numbers, which are generally positive. The growth forecasts for EAP for 2013 and 2014 remain roughly similar to those of December last year. Both the global and regional outlooks are subject to several risks, most of which are by now familiar. Though the developing economies of East Asia are generally well-prepared to absorb external shocks, an emerging concern is the risk of over-heating in some of the larger economies in the region. Policy makers in developing EAP should strive to strike the right balance between managing the near-term risks, and sustaining and increasing inclusive growth in the medium-term by enhancing the underlying productive capacity-human and physical-of these economies.